The Cooks of The Canterbury Tales: The Backstage of Bourgeois Social Drama - Oya BAYILTMIŞ ÖĞÜTCÜ (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2016)
Despite their rise in the social ladder, the newly emerging bourgeoisie of late medieval England needed to display their wealth not only to secure their place in the social hierarchy, but also to receive acceptance from noble people in their communities. Hence, the public and private lives of the medieval English bourgeoisie turned out to be arenas for social drama, as conceptualized by Victor Turner, in which their cooks and kitchens were important as backstage elements as exemplied by the cook of the Franklin and the Cook of the Guildsmen in Chaucer's Canterbury Tales. Therefore, this article aims at analysing Chaucer's depiction of the cooks in the Canterbury Tales, and to discuss their function in contributing to the social changes as gures at the backstage of bourgeois social drama. In line with this, this article argues that the cooks were indispensable for the medieval bourgeoisie to sustain their social drama through the use of food culture.